Adherence with blood pressure self-monitoring in women with pregnancy hypertension, and comparisons to clinic readings: A secondary analysis of OPTIMUM-BP - Bowen, L; Pealing, L; Tucker, K; McManus, RJ; Chappell, LC (Elsevier, 2021)
Objectives To assess adherence to self-monitoring of blood pressure (SMBP), and differences between SMBP and clinic readings, in a self-monitoring intervention for managing pregnancy hypertension. Study design OPTIMUM-BP was an unmasked randomised controlled clinical trial. 154 women with pregnancy hypertension from four maternity units in England were recruited and randomised to SMBP or usual care. This secondary analysis included 91 women randomised to self-monitoring who provided BP readings. Trial instructions were for daily SMBP. Main outcome measures Adherence was calculated as proportion of days on which SMBP readings were taken. Proportion of weeks in which at least 4 and at least 2 SMBP readings were taken was also calculated. Mean differences between clinic and SMBP measurements were calculated. Results Self-monitored BP data were available for 49 women with chronic hypertension and 42 women with gestational hypertension. Median percentage of days with SMBP readings was 77% (IQR 51, 89) in the chronic hypertension group and 85% (IQR 52, 95) in the gestational hypertension group. Adherence did not vary by different socio-demographic groups. Mean difference (95% CI) between clinic and SMBP for systolic BP was 0.99 mmHg (−1.44, 3.41; chronic hypertension) and 3.76 mmHg (0.75, 6.78; gestational hypertension) and for diastolic BP was 3.03 mmHg (0.93, 5.12; chronic hypertension) and 3.27 mmHg (0.56, 5.98; gestational hypertension). Conclusions Adherence to self-monitoring was good and differences between SMBP and clinic readings were small. These findings offer reassurance about the use of self-monitoring at a time when it is being increasingly implemented in maternity settings.